Validity of an Ethnomathematics Integrated Mathematics E-Module for Phase F Students at SMAN 1 Koto XI Tarusan - Kiki Ardila Putri; Teni Suriani; Nela Sari Yolanda (The Future of Education Journal, 2026)
Mathematics learning at SMA Negeri 1 Koto XI Tarusan was marked by teacher-centred explanation, limited digital teaching materials, and weak connections between mathematical ideas and students' experiences. Semester assessment records showed that 109 of 119 Phase F students, or 91.60%, had not reached the school minimum mastery criterion of 80. This study developed and examined the validity of an ethnomathematics-integrated mathematics e-module on systems of linear equations in two and three variables. The topics were selected as a gradual reinforcement of linear modelling from two variables to three variables, based on the school needs analysis. This Research and Development study used the 4D model. The article was limited to the define, design, and develop stages because the disseminate stage could not be carried out within the available research time. Three content experts, three design and graphics experts, and one language expert, assigned in accordance with institutional guidance, assessed the prototype. The validation results were 81.77% for content, 87.50% for design and graphics, and 86.36% for language. The combined score percentage was 84.47%, which falls into the highly feasible category. The e-module can proceed to practicality testing after revisions to conceptual accuracy, links between cultural contexts and mathematical models, information density, and sentence clarity.